The new superpowers : - Bergner, Jeffrey T. (St. Martin's Press, 1991)
Bergner, former chief of staff for the Senate Committee on Foreign Relations, has written a thoughtful and well-reasoned analysis of the new alignments taking place in international relations. Bergner sees the century ending with the Soviet Union in decline and the reemergence of Japan and a united Germany. He surveys their growing political and economic power and buttresses his text with numerous charts and tables. Bergner argues that the United States will have to stay involved militarily as well as politically in Europe and Asia to maintain a peaceful future. While not as strident as George Friedman and Meredith Lebard's The Coming War with Japan ( LJ 5/15/91), Bergner emphasizes the danger to stability if the United States were to renew its isolationist tendencies as the Cold War ends. Highly recommended.